2017
DOI: 10.3389/fmars.2017.00257
|View full text |Cite
|
Sign up to set email alerts
|

Why Conferences Matter—An Illustration from the International Marine Conservation Congress

Abstract: A major activity in the life of an academic is the professional conference. It is common knowledge that this is a place to present your research, but what about other benefits of attending a conference? Online surveys were distributed to delegates of the 3rd and 4th International Marine Conservation Congresses (IMCCs), with respondents' (n = 100) feedback including that the congresses provided useful new information that will aid: (1) their research (58%); (2) in-the-field conservation (29%); (3) conservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
78
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 25 publications
1
78
1
5
Order By: Relevance
“…Online communities can support learning and identity formation (Hall, 2009;Reed, 2013), but they do not foster the substantive interdisciplinary conversations needed to advance ISC as a cohesive intellectual framework. Conferences can generate awareness, ideas, collaborations, and dialogue (Hatcher et al, 2006;Oester et al, 2017), yet, there are few in-person opportunities for ISC researchers or practitioners to network.…”
Section: A Model For Building Community To Advance Inclusive Sciencementioning
confidence: 99%
“…Online communities can support learning and identity formation (Hall, 2009;Reed, 2013), but they do not foster the substantive interdisciplinary conversations needed to advance ISC as a cohesive intellectual framework. Conferences can generate awareness, ideas, collaborations, and dialogue (Hatcher et al, 2006;Oester et al, 2017), yet, there are few in-person opportunities for ISC researchers or practitioners to network.…”
Section: A Model For Building Community To Advance Inclusive Sciencementioning
confidence: 99%
“…A truly relevant difference between virtual vs in-person conferences is the quality of communications [2]; several studies and research on deliberative methods have demonstrated that learning and collaboration are facilitated during two-way exchanges [3]. Although a speech or a presentation can be viewed by an unlimited number of the people, streaming video only facilitate one-way communication.…”
mentioning
confidence: 99%
“…Although a speech or a presentation can be viewed by an unlimited number of the people, streaming video only facilitate one-way communication. For multiway communication to occur, online meetings should allow attendees to interact and ask questions; however, web conferencing can only accommodate a limited number of people, and at present tens or hundreds of attendees cannot interact together effectively [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations